A new genus of water mites (Acari, Hydrachnidia, Wettinidae) from bromeliad phytotelmata in the Brazilian Atlantic rainforest - Pesic, Vladimir; Oliveira Piccoli, Gustavo Caue de [UNESP]; Araujo, Marcel Santos de [UNESP]; Rezende, Jose Marcos [UNESP] (Pensoft Publ, 2015)
Adults of Bromeliacarus cardoso gen. n., sp. n. are described from phytotelmata of Quesnelia arvensis (Vellozo) Mez. (Bromeliaceae) in the subtropical area of the Atlantic rainforest, Sao Paulo State, Brazil. The new genus Bromeliacarus is proposed and diagnosed, based primarily on the autapomorphic presence of 7-9 pairs of acetabula flanking the gonopore. A possible relationship between Bromeliacarus and other Wettinidae are discussed.
Keywords: Water mite; new genus; taxonomy; Brazil